PERAN STAKEHOLDER PADA ASPEK KONSERVASI DALAM PENGELOLAAN TAMAN NASIONAL LAUT KEPULAUAN SERIBU (TNKpS) - Eka Dana Prabowo; Harnios Arief; Tutut Sunarminto (Media Konservasi, 2015)
The TNKpS area was marine consist of 110 small land with 108 land outside management authority of TNKpS and five of which are settlement land which occupied by 14,061 people. Beside the area condition, management complexities were actualization of protection, preservation, and utilization of natural resources in TNKpS. To overcome the management complexities, collaboration with other stkakeholders were needed so that the goals of management could be achieved. The purpose of this research is to identify the main role of stakeholder in conservation aspects. Research was done on the all of TNKpS’ SPTN at the islands where the stakeholder standby, using a closed-ended questionnaire method to 77 indicator in 11 criteria, and analyzed as descriptive. Stakeholders consist of government institutions, private sectors, NGOs, and the communities organization. Positive roles were the dominant to conservation activities. The stakeholder role focused on certain indicator that appropriate with organization main function and goals along with collaboration agreement. The role that less only the management of abration and intrution, utilization, and carrying capacity has not been done by all of the stakeholders.  Keyword: collaboration, management complexities, role, stakeholders, TNKpS